Publikationskosten für Zeitschriftenartikel abseits von Open-Access-Publikationsfonds – Lost in Transformation? - Frick, Claudia; Kaier, Christian (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2020)
While Open Access is being established as the standard model of scholarly publishing, the focus is shifting from subscription to publication costs. Identifying and allocating these costs in a complete and reliable way poses major challenges to both libraries and institutions. This is due to decentralized invoicing workflows, various business models, supplementary publishing fees, and a coexistence of individual and lump-sum publishing fees as well as a mixing of subscription and publication costs. This article first outlines the wide range of different publication costs for journal articles. It subsequently presents two approaches for compiling dispersed publication costs to ensure better management and more transparency of the expenses involved in scholarly publishing.